2015
DOI: 10.1111/chd.12269
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Neurodevelopment Using Bayley-III in Children with Cyanotic or Hemodynamically Impaired Congenital Heart Disease

Abstract: This study demonstrated that children with cyanotic or hemodynamically impaired CHD have delayed neurodevelopmental outcomes compared with healthy children as assessed using Bayley-III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 15 publications
1
15
0
8
Order By: Relevance
“…43 Although all children benefited from indirect intervention through educational support and recommendations of activities and exercises to parents, a few of them received additional care regarding language development. While we observed similar language performances compared to studies using Bayley-III during the first two years of life in children with CHD, 10,11 our study group exhibit higher intellectual functioning. This discrepancy may reflect the beneficial effect of early and systematic multidisciplinary surveillance in this population.…”
Section: Language Outcome and Trajectorysupporting
confidence: 69%
See 1 more Smart Citation
“…43 Although all children benefited from indirect intervention through educational support and recommendations of activities and exercises to parents, a few of them received additional care regarding language development. While we observed similar language performances compared to studies using Bayley-III during the first two years of life in children with CHD, 10,11 our study group exhibit higher intellectual functioning. This discrepancy may reflect the beneficial effect of early and systematic multidisciplinary surveillance in this population.…”
Section: Language Outcome and Trajectorysupporting
confidence: 69%
“…1,9 At 15 months of age, children with CHD obtain lower scores (on average 10 to 17 points lower) on standardized language assessments for both expressive and receptive skills compared to healthy children, with more significant impairments in expressive compared to receptive skills. 10,11 At 21 months of age, the language impairment rate of 15.5% largely exceed normative expectations, whereas rates of cognitive impairments remain in the normal range ( 2.27%). 11 Speech and language delays seem to persist, as the proportion of children showing abnormal language development generally increases with age.…”
Section: Introductionmentioning
confidence: 92%
“…The Bayley-III has mainly been evaluated for use with children born preterm (Reuner, Fields, Wittke, Löpprich, & Pietz, 2013;Spencer-Smith, Spittle, Lee, Doyle, & Anderson, 2015;Velikos et al, 2015) or with medical conditions (Acton et al, 2011;Hallioglu et al, 2015;Komur, Ozen, Okuyaz, Makharoblıdze, & Erdogan, 2013). These studies, as well as the technical manual of the Bayley-III (Van Baar, Steenis, Verhoeven, & Hessen, 2014), describe the scores of the children on the Bayley-III.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown how much CHD can affect motor 3,4,5 , cognitive and language development of infants 5 . It is known that neuropsychomotor development (NPMD) can be influenced from biological, psychological, social and environmental factors 6 .…”
Section: Introductionmentioning
confidence: 98%